2018
DOI: 10.1136/bmjqs-2017-007218
|View full text |Cite
|
Sign up to set email alerts
|

Perceptions of rounding checklists in the intensive care unit: a qualitative study

Abstract: Our results provide potential insights about why ICU rounding checklists frequently fail to improve outcomes and offer a framework for effective checklist implementation through greater feedback and accountability.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
20
0
6

Year Published

2018
2018
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 20 publications
(26 citation statements)
references
References 17 publications
0
20
0
6
Order By: Relevance
“…These approaches to promoting the checklist to staff were employed strategically to encourage take-up. However, the emphasis on administrative discourses undermine the clinical status of checklists and make them less likely to be completed during busy times (Aveling et al, 2013;Hallam et al, 2018).…”
Section: Discussionmentioning
confidence: 99%
“…These approaches to promoting the checklist to staff were employed strategically to encourage take-up. However, the emphasis on administrative discourses undermine the clinical status of checklists and make them less likely to be completed during busy times (Aveling et al, 2013;Hallam et al, 2018).…”
Section: Discussionmentioning
confidence: 99%
“…We postulated that by infiltrating the rounding process at various levels, we would increase reliability of discussion of key care goal topics, which was our outcome measure of interest. The integrated use of rounding checklists or templates has been previously suggested by Hallam et al 10 as being fundamental to success based on their qualitative study of the perception of ICU rounding checklists by providers. Other studies have found the integration of checklists into the EHR beneficial.…”
Section: Discussionmentioning
confidence: 99%
“…Similarly, this phenomenon was noted by Newkirk et al 14 in their study on prompted ICU rounding checklist use, in which they showed that discussion of checklist topics before prompting increased on rounds as the study period progressed. 10…”
Section: Discussionmentioning
confidence: 99%
“…It allows aligning and standardizing the activities performed by HMB, besides functioning as a reminder for the application of the best evidence (31) . Its application has been increasingly common in the health area, and has demonstrated potential to be used as a standardization and communication tool in the Intensive Care Unit, to increase safety and avoid errors (32) .…”
Section: Tools To Improvement Of Processesmentioning
confidence: 99%